G53(P) The rising incidence of classical and non-classical coeliac disease in Southeast Scotland – a 5 year review. (27th April 2016) - Lister, MF; Mckerrow, L; Menzies, E; Tybulewicz, A; Rosie, L; Gillett, P
Abstract : Background: The incidence of coeliac disease (CD) is increasing in many countries. Aim: To update previous research 1, 2 on incidence and presentation of CD in Southeast Scotland (SES). Subjects: All those under 16 years diagnosed with CD in SES from the 1st of January 2010 to the 31st of December 2014. Methods: Positive anti-tissue transglutaminase (anti-TTG) results from SES are reported to the lead for the regional service and followed up. Our regional database was cross-checked against local databases as a retrospective audit. All serology tests requested in under 16's in Lothian and Fife (these go to a central laboratory) were assessed as a proxy for increasing awareness. Results: 224 patients (149 female, 75 male) were diagnosed. Median age was 7.5 years (range: 1 year 65 days to 16 years). In 2010 there were 31, 2011: 37, 2012: 49, 2013: 54 and in 2014: 53 patients identified. Incidence increased from 2010 to 2014 (13.6 to 23.2/100 000 respectively). Classical cases 3 rose from 6.6/100 000 in 2010 to 14/100 000 in 2014. Non-classical cases rose from 3.9 to 8.3/100 000 between 2010 and 2014. 16 asymptomatic cases were identified by screening individuals with associated conditions, and in 6 cases the presentation was unknown. There has been an increase in the number of anti-TTG requests from 2274 in 2010 to 3489 in 2014. The percentage of positive tests rose. Summary: We performed a retrospective analysis of cases of CD over a 5 year period. The incidence of classical and non-classical presentations continues to rise. The percentage of positive results has risen, confirming a true rise in the incidence of coeliac disease. Better awareness and a lower threshold to test is clearly good. Comparison of variations with other regions in the UK is crucial for clinicians and Coeliac UK to help target awareness and improve diagnosis. References: White LE, et al . The Rising incidence of Celiac Disease in Scotland. Paediatrics . 2013;132 (4):924–3 White LE, et al . Childhood Coeliac Disease Diagnoses in Scotland 2009-2010: The SPSU Project. Arch dis Child . 2013;98 :52–56 Ludvigsson, et al . The Oslo Definitions for Coeliac Disease and Related Terms. Gut . 2013;62 (1):43–52